2005
DOI: 10.1016/j.jacc.2004.11.047
|View full text |Cite
|
Sign up to set email alerts
|

The need for atrial flutter ablation following pulmonary vein antrum isolation in patients with and without previous cardiac surgery

Abstract: In patients with PCS, post-PVAI AF recurrence is similar to patients without PCS. However, history of PCS is associated with a higher recurrence of AFL after PVAI. In a significant number of patients with PCS, AFL ablation is required to achieve a cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Prior case reports have noted new onset LA Flrs occurring after PV isolation, 6,8–10 circumferential LA ablation, 3,11–14 as well as after intraoperative radiofrequency ablation for management of atrial fibrillation 7 . A retrospective study by Mesas et al described successful ablation of LA Flrs/tachycardias in 5% of patients 2.6 ± 1.6 months after circumferential PV ablation for atrial fibrillation 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior case reports have noted new onset LA Flrs occurring after PV isolation, 6,8–10 circumferential LA ablation, 3,11–14 as well as after intraoperative radiofrequency ablation for management of atrial fibrillation 7 . A retrospective study by Mesas et al described successful ablation of LA Flrs/tachycardias in 5% of patients 2.6 ± 1.6 months after circumferential PV ablation for atrial fibrillation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Circumferential ablation within the left atrium has been used as curative therapy for atrial fibrillation 1–4 and has been reported to significantly reduce atrial fibrillation in comparison to pulmonary vein (PV) isolation 2,5,6 . Prior studies have also reported upon the occurrence of left atrial tachycardias/flutters (LA Flr) after circumferential ablation 7–14 . The purpose of this prospective trial is to define the frequency of inducible LA Flr immediately after circumferential LA ablation, to assess whether inducibility predicts new onset clinical LA Flr, and to report upon the management of LA Flr.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was congruent with a ninefold higher AT incidence in patients with persistent forms of AF reported by Porter et al (2,4% versus 20%) [42]. Actually, this is not the case because the proportion of patients with persistent/chronic AF in the studies in which CPVA plus lines was used reached 17%–36,5% [1518, 20, 21, 24, 26, 27], a percentage similar to that reported in the series in which segmental or circumferential antral PV isolation was performed (8%–43%) [23, 24, 3339]. As a consequence, factors directly linked to the ablation technique in itself seem to determine the PAFAT incidence, although the scarce studies that have compared both techniques have yielded conflictive results [43, 44].…”
Section: Incidencementioning
confidence: 87%
“…This latter figure is even higher in patients with previous cardiac surgery [23]. In addition, the reported incidence of PAFAT is probably underestimated in most of these series because only symptomatic patients were referred for a new ablation procedure [21, 24].…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation